The Correlation Between Crime Frequency and Urban Spatial Hierarchy in Busan - Yao Lu; Shan Gao; Tingting Hong; Zhe Cao; Heangwoo Lee; Eunkil Cho; Xiaolong Zhao (Buildings)
This study examined the relationship between urban spatial hierarchy and crime rates in Busan using space syntax. This research study investigated the correlation between crime frequency and Busan’s urban space structure. The findings are as follows. Crime concentrated in areas near downtown Busan. High-control and globally integrated areas showed a strong link between city center crimes and spatial usage patterns and pedestrian routes. A weak positive correlation was found between Busan’s urban spatial hierarchy and crime frequency, indicating that urban spatial hierarchy influences crime patterns. However, the regression model’s independent variables had low explanatory power for the dependent variable, suggesting external factors influence crime occurrence beyond urban spatial hierarchy. This study provides an empirical analysis of the relationship between crime incidence and urban spatial structure in Busan, serving as essential data for future crime prevention policies.